Analysis of the Determination of Production Costs in Rice Farming in Padas Village, Tanon District - Haryanto, Wawan (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The agricultural sector is very helpful for the people's economy in the business world in accounting science to calculate the cost of production with careful calculations will provide benefits to minimize losses that can occur, and can cultivate the calculation of crop production, fertilizer and drug costs, capital interest, equipment depreciation, labor costs, in this study, the method used is purposive sampling with the consideration that the rice production area of the Padas village area with the Research Hamlet is Concluded as follows: The largest total cost expenditure in this study per hectare is the highest in Sukorjo Hamlet Rp. 29,895,118 while the smallest cost expenditure is 1 while the highest price of rice is Dadapan Rp. 6,127 while the lowest price is Rp. 2,341. The limitations of the research from the variables I use are only Padas Village, maybe the research can do many variables.